Protocol for the visualization of pRps6-positive cells in larval zebrafish brains using whole-mount immunofluorescence and light-sheet microscopy - Olga Doszyn; Tomasz Dulski; Justyna Zmorzynska (STAR Protocols)
Summary: Due to their small size and transparency, larval zebrafish are a useful model for whole-brain imaging. Here, we present a protocol for the visualization of phosphorylated Rps6, a marker of mechanistic target of rapamycin complex 1 (mTORC1) activity, in the zebrafish brains at 5 days post fertilization (dpf), using whole-mount immunofluorescence and light-sheet microscopy. We describe steps for sample preparation, storage, staining, and imaging. This protocol can also be modified for staining with antibodies against other proteins.For complete details on the use and execution of this protocol, please refer to Doszyn et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.